2003
DOI: 10.1074/jbc.m300102200
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-secreting β-Cell Dysfunction Induced by Human Lipoproteins

Abstract: Diabetes is associated with significant changes in plasma concentrations of lipoproteins. We tested the hypothesis that lipoproteins modulate the function and survival of insulin-secreting cells. We first detected the presence of several receptors that participate in the binding and processing of plasma lipoproteins and confirmed the internalization of fluorescent low density lipoprotein (LDL) and high density lipoprotein (HDL) particles in insulin-secreting ␤-cells. Purified human very low density lipoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
135
1
8

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(165 citation statements)
references
References 29 publications
14
135
1
8
Order By: Relevance
“…Our results complement those on lipoprotein-induced beta cell dysfunction [18] to suggest that changes in plasma lipoproteins observed in type 2 diabetes may not only be a consequence of this disease but also a cause of it.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results complement those on lipoprotein-induced beta cell dysfunction [18] to suggest that changes in plasma lipoproteins observed in type 2 diabetes may not only be a consequence of this disease but also a cause of it.…”
Section: Discussionsupporting
confidence: 85%
“…According to a widely held view, these characteristic changes in lipoprotein pattern are a consequence of insulin resistance and type 2 diabetes. However, a recent study using mouse pancreatic islets and a transformed insulin-secreting beta cell line demonstrated that purified TGRL and LDL particles may induce insulin-secreting beta cell dysfunction, indicating that the changes in plasma lipoproteins characteristic of type 2 diabetes are not only a consequence but also a cause of this disease [18]. To our knowledge, however, nothing is known as to whether intact lipoprotein particles are also capable of inducing insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Des études menées chez la souris montrent que l'invalidation de ABCA1 dans l'ensemble des tissus entraîne une intolérance au glucose mais est sans effet sur la sensibilité à l'insuline [10]. Lorsque l'invalidation d'ABCA1 est restreinte aux seules cellules , il n'y a pas d'altération systémique SYNTHÈSE REVUES un grand nombre de modèles cellulaires : cultures primaires d'îlots et de cellules  isolés de tissus humains et de rongeurs (rat et souris) [13,14], ou lignées tumorales de souris comme MIN-6 et TC3 [14], de rat comme les INS-1 [15] ou encore de hamster, les HIT-15 [16]. Les VLDL, les LDL et les HDL ont la capacité de modifier la fonction et la survie des cellules .…”
Section: Rôle Des Lipoprotéines Et Du Récepteur Au Ldl Sur La Fonctiounclassified
“…Les VLDL, les LDL et les HDL ont la capacité de modifier la fonction et la survie des cellules . L'exposition aux LDL in vitro est toxique pour ces cellules [4] : elle induit la mort par nécrose des cellules  isolées de rat et par apopotose des îlots isolés de souris [14], et une diminution de l'ARNm de l'insuline. De même, l'exposition aux VLDL apparaît délé-tère pour les cellules  [14].…”
Section: Rôle Des Lipoprotéines Et Du Récepteur Au Ldl Sur La Fonctiounclassified
See 1 more Smart Citation